Effect of Oyster Mushroom on Kidney in Stress Induced Depressed Rats - Jahan, Nasim; Akhter, Sharmin; Sultana, Nahid (Journal of Bangladesh Society of Physiologist, 2017)
Background: Depression is associated with stressful condition which may cause kidney damage. Oyster mushroom (plurotus florida) may have free radical scavenging activity thereby can be used for the prevention and treatment for kidney damage. Objective: to observe the effect of oyster mushroom (plurotus florida) on kidney in restraint stress induced depressed rats. Methods: This experimental study was conducted from July 2012 to June 2013 in the Department of Physiology, Sir Salimullah Medical College( SSMC), Mitford, Dhaka. Thirty Wister albino male rats, aged 90 to 100 days, weighing 150 to 180g (initial body weight) were used in the present study. Then they were divided into Group I (Control group, without mushroom n=20) and Group II (Experimental group, depressed rats supplemented with mushroom n=10). Control group without mushroom again subdivided into Group Ia,( baseline control n=10) and Group Ib (depressed control n=10) . All groups of animals were received basal diet for 28 consecutive days started from the 1st day of the study period. Group Ib (depressed control) and group II (depressed mushroom supplemented) were housed under controlled condition in rat immobilizer (made up of steel wire, measuring 9´´x2.75´´ of light weight) for 6 hour/day for 28 days for the development of stress induced depression. In addition, only group II received oyster mushroom extract (200 mg/kg body weight, orally) for the same period. One rat of Group Ib (depressed control) was expired after 10 days for unknown cause. All 29 rats were sacrificed on day 30. Then blood sample and kidneys specimen were collected. Initial (initial bw ) and final body weights (final bw) were measured. Then estimation of blood glucose and serum urea levels were done by standard laboratory technique. Histology of kidney was done by standard laboratory procedure. Statistical analysis was done by using SPSS windows Version -16. One way ANOVA and Bonferroni tests were done as applicable. Results: In this study blood glucose level and serum urea level was significantly higher and abnormal histological structure was found in stress induced depressed rats. After taking mushroom extract for 28 days all the parameters were improved. Conclusion: From this study it can be concluded that oyster mushroom(Pleurotus florida) which is excellent edible and nutritious, may have renoprotective effect. Bangladesh Soc Physiol. 2017, June; 12(1): 33-40